2020
DOI: 10.3390/cancers12071922
|View full text |Cite
|
Sign up to set email alerts
|

CN133, a Novel Brain-Penetrating Histone Deacetylase Inhibitor, Hampers Tumor Growth in Patient-Derived Pediatric Posterior Fossa Ependymoma Models

Abstract: Pediatric ependymoma (EPN) is a highly aggressive tumor of the central nervous system that remains incurable in 40% of cases. In children, the majority of cases develop in the posterior fossa and can be classified into two distinct molecular entities: EPN posterior fossa A (PF-EPN-A) and EPN posterior fossa B (PF-EPN-B). Patients with PF-EPN-A have poor outcome and are in demand of new therapies. In general, PF-EPN-A tumors show a balanced chromosome copy number profile and have no recurrent somatic nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We established three SC lines (two of them from two patients with PF-EPN-A and one from a patient with an ST-EPN) that grow in a serum-free medium with the epidermal growth factor/fibroblast growth factor [ 31 , 32 , 33 ]. We also generated derivative subclones by differential selective pressure exerted by omission of mitogens and/or heterotopic selection in vivo, these model systems reflecting tumor subpopulations which adapt to microenvironment constraints, e.g., to nutrient/growth factor deprivation, such as those which occur in necrotic tumor areas [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We established three SC lines (two of them from two patients with PF-EPN-A and one from a patient with an ST-EPN) that grow in a serum-free medium with the epidermal growth factor/fibroblast growth factor [ 31 , 32 , 33 ]. We also generated derivative subclones by differential selective pressure exerted by omission of mitogens and/or heterotopic selection in vivo, these model systems reflecting tumor subpopulations which adapt to microenvironment constraints, e.g., to nutrient/growth factor deprivation, such as those which occur in necrotic tumor areas [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PF cell lines EPP, EPP-MI, EPV, EPV-FL and EPV-FL-MI were established in our laboratory and previously characterized for stemness-defining features, e.g., expression of neural stemness markers, neurosphere-forming ability, self-renewal, long-term propagation and tumor-initiating capability in nude mice [ 31 , 32 , 33 ]. All the EPN lines used in this study were grown in 3D conditions in a Neurocult medium ( STEMCELL Technologies, Cambridge, UK) supplemented with 20 ng/mL EGF (Sigma-Aldrich, St. Louis, MO, USA) and 10 ng/mL FGF2 (Promega, Madison, WI, USA), a well-validated culture condition to favor neural stem-like cell growth [ 15 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the promising results of pre-clinical research [ 88 , 89 ], histone deacetylase (HDAC) inhibitors showed no therapeutic activity in patients, apparently due to the intricacies of subcellular localization of HDACs and inability of the inhibitors to accumulate inside the brain tissue in concentrations sufficient for therapeutic response [ 90 ]. Nevertheless, the search for new HDAC inhibitors with appropriate brain-penetrating capacities and safety profiles may provide a useful treatment strategy [ 91 ]. The possibility of using BET-bromodomain inhibitors as anticancer therapeutics is being investigated in pediatric EPN stem cell models [ 92 ].…”
Section: Therapeutic Targeting Of Epnsmentioning
confidence: 99%
“…In PF-Neuronal-Precursor-like cells, targetable pathways might be the epigenetic regulators HDAC2, DNMT3A, and BRD3. Indeed, the pan-HDAC inhibitor CN133 [ 215 ] and the HDAC2 inhibitor panobinostat [ 165 ], as well as the pan-BRD inhibitors JQ1 [ 199 ] and OTX012 [ 216 ], have been reported to decrease cell viability and tumor growth in patient-derived PFA cell lines. Emerging epigenetic therapies under evaluation in clinical trials for brain tumors, including EPN, have been reviewed recently [ 217 ].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%